Gamification-Based Emotional Connectivity Model: Strengthening Positive Classroom Relationships to Reduce Student Academic Burnout - Zakiyah BZ; Devi Fitriatin; Sri Suciani; Siti Nur Kholisa (Managere: Indonesian Journal of Educational Management, 2025)
Academic burnout is a complex emotional condition that arises from prolonged learning pressure and weak social connections in the classroom. This study examines the effectiveness of a Gamification-Based Emotional Connectivity Model as an innovative management strategy to enhance emotional bonds between teachers and students, while reducing symptoms of academic burnout. Using a qualitative approach that incorporated participatory observation, in-depth interviews, and documentation, the research was conducted in classrooms where students had previously exhibited signs of emotional fatigue and disengagement. The gamification model integrates game-based learning elements—such as points, badges, and collaborative challenges—with emotional reinforcement through empathy, positive feedback, and reflective sharing. The findings suggest that gamification has a significant impact on enhancing the classroom climate, thereby creating a more supportive and participatory learning environment. Students who were previously passive became more active and confident in expressing their ideas, while teachers acted as emotional facilitators rather than mere instructors. The study identifies four key dimensions that support emotional well-being in learning: emotional safety, positive reinforcement, collaborative interaction, and teacher emotional presence. Through these dimensions, the gamification model transforms learning into a psychologically safe, socially engaging, and intrinsically motivating process. The results indicate that integrating emotional connectivity into gamified learning not only increases motivation and engagement but also serves as a preventive framework against academic burnout. This model offers a practical contribution to developing emotionally intelligent classrooms and advancing the pedagogy of well-being in modern education.